Non-clausal temporal adverbials in fiction - Žáková, Monika (Univerzita Pardubice, 2011)
This bachelor paper focuses on non-clausal temporal adverbials in fiction. The theoretical part characterizes their semantic categories, syntactic realization and the most frequent positions in the clause. Furthermore, it deals with the relationship between temporal adjuncts and verbs in term of the category of tense and aspect. In the practical part, there is introduced and described the style of fiction and further, the findings from the theoretical part are applied to analysis of chosen text in the fiction style in order to state the results of research.
Nevětná časová adverbia ve fikci
Keywords: adjunkty; umělecká literatura; pozice ve větě; čas; adjuncts; fiction; position in the clause; tense